Intelligent Analysis of Quasiperiodic Bioosignals in Medical Diagnostic Problems (with the Example of a Pulse Signal) - Desova, A. A.; Guchuk, V. V.; Pokrovskaya, I. V.; Dorofeyuk, A. A. (Automation and remote control, 2018)
We identify the main stages of intelligent analysis of the pulse signal of the radial artery, used to obtain a set of informative parameters in medical diagnostic problems for various diseases. We show the results of expert and formalized classifications of the parameters of the analyzed signal, including the parameters of the shape of the pulse wave within the main quasiperiod and parameters that determine the rhythmic structure of the signal. We develop a multi-stage scheme for obtaining a set of informative parameters of the pulse signal that allows to take into account their characteristic features. The effectiveness of the developed approaches is demonstrated with the example of the problem of diagnosing early stages of arterial hypertension.